I Am as Incompetent as the Prototypical Group Member: An Investigation of Naturally Occurring Golem Effects in Work Groups - Leung, Alex; Sy, Thomas (Frontiers in Psychology, 2018)
Over four decades, research has demonstrated Pygmalion and Galatea effects (positive expectations leading to high performance) across various settings. In contrast, research on the parallel notion of Golem effects (negative expectations leading to low performance) has been largely overlooked. This study is the first to examine the relationship between group-level Implicit Followership Theories (GIFTs) and naturally occurring Golem effects. Integrating the literature on Implicit Followership Theories, self-fulfilling prophecies, and social identity, we propose that negative GIFTs can serve as proxies of expectations for followers that trigger Golem effects in workgroups. Data from 202 followers and 101 leaders provide support for our hypothesized multi-level model, revealing a top-down relationship between negative GIFTs and follower performance through their self-efficacy and effort. Findings highlight the importance of GIFTs in the Golem process, showing that followers’ cognitions and behaviors are shaped by the group’s prototypical attributes. Suggestions for future research are offered, including interpersonal Golem effects, negative GIFTs and negative outcomes, and influence of organizational culture.